Maximal strength training improves work economy, rate of force development and maximal strength more than conventional strength training - Heggelund, J.; Fimland, M. S.; Helgerud, J.; Hoff, J. (European Journal of Applied Physiology, 2013)
This study compared maximal strength training (MST) with equal training volume (kg × sets × repetitions) of conventional strength training (CON) primarily with regard to work economy, and second one repetition maximum (1RM) and rate of force development (RFD) of single leg knee extension. In an intra-individual design, one leg was randomized to knee-extension MST (4 or 5RM) and the other leg to CON (3 × 10RM) three times per week for 8 weeks. MST was performed with maximal concentric mobilization of force while CON was performed with moderate velocity. Eight untrained or moderately trained men (26 ± 1 years) completed the study. The improvement in gross work economy was -0.10 ± 0.08 L/min larger after MST (P = 0.011, between groups). From pre- to post-test the MST and CON improved net work economy with 31 % (P < 0.001) and 18 % (P = 0.01), respectively. Compared with CON, the improvement in 1RM and dynamic RFD was 13.7 ± 8.4 kg (P = 0.002) and 587 ± 679 N s-1 (P = 0.044) larger after MST, whereas isometric RFD was of borderline significance 3,028 ± 3,674 N s-1 (P = 0.053). From pre- to post-test, MST improved 1RM and isometric RFD with 50 % (P < 0.001) and 155 % (P < 0.001), respectively whereas CON improved 1RM and isometric RFD with 35 % (P < 0.001) and 83 % (P = 0.028), respectively. Anthropometric measures of quadriceps femoris muscle mass and peak oxygen uptake did not change. In conclusion, 8 weeks of MST was more effective than CON for improving work economy, 1RM and RFD in untrained and moderately trained men. The advantageous effect of MST to improve work economy could be due to larger improvements in 1RM and RFD.